HAK PENCIPTA FILM TERHADAP KARYANYA YANG DIBAJAK SECARA ILEGAL PADA WEBSITE LK21 - Jason Marcellino; Imelda Martinelli; Reisa Arrifa (LPPM Universitas Ekasakti Padang, 2023)
Due to the rise in cases of film piracy in Indonesia, this has motivated the writer to conduct research on this case. By using a qualitative descriptive writing method, the data is obtained from observations and also from literature studies. The concludes from the author's research, someone who uploads a film without any permission from relevant party can be declared as film piracy, but unfortunately there are still many people who even support this. Because if you watch through illegal websites it is free, but they arn’t aware that this act is a violation of the ITE Law. The main factor is that the perpetrators of piracy get a lot of profit from the audience, and also get a good response from the public who prefer to use illegal websites rather than using illegal websites. with a legal film player application. Stopping film piracy carried out by the LK 21 website has been terminated by blocking the lk 21 website by the Ministry of Communication and Informatics, for viewers to be wiser by watching films through the official site or application so that piracy does not occur.